2021
DOI: 10.1515/pthp-2021-0006
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of two intensive decontamination protocols and their effects after 30 days on environmental contamination by cyclophosphamide

Abstract: Objectives To evaluate the efficacy of two decontamination protocols on cyclophosphamide surface contamination and to explore its lasting effect 30 days later. Methods All sampling sites that were systematically contaminated with cyclophosphamide in 2017–2020 were included, from a convenience sample of centers. The first decontamination protocol consisted of four steps, each with 20 mL and a Wypall® wipe: detergent, sodium hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Many other studies in the literature have shown that ADs are still regularly detected on surfaces in healthcare centers despite the specific decontamination protocols implemented. 14,40,41 NIOSH alert 2004 recommended establishing some decontamination procedures, particularly for cleaning up spillage in cases of accidental exposure. 5 On this point, our study suggests that the procedures were insufficiently known by OR caregivers and not fully known by CU caregivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many other studies in the literature have shown that ADs are still regularly detected on surfaces in healthcare centers despite the specific decontamination protocols implemented. 14,40,41 NIOSH alert 2004 recommended establishing some decontamination procedures, particularly for cleaning up spillage in cases of accidental exposure. 5 On this point, our study suggests that the procedures were insufficiently known by OR caregivers and not fully known by CU caregivers.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the implementation of safety measures, recent studies have still reported residual contamination with ADs on surfaces and on caregivers’ hands. 13,14…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, an intensive decontamination session proved to have a lasting effect on shelves, but biological safety cabinets and floors rapidly became contaminated again after typical daily drug preparation activities were resumed. 22 In addition, workers may be less prone to wearing their PPE in areas where the contamination risk is perceived as lower.…”
Section: Monitoring Programmentioning
confidence: 99%